A wire transposition technique for recanalization of chronic complex central venous occlusions. (February 2016) - Massmann, A; Rostam, A; Fries, P; Buecker, A
Purpose: A minimal-invasive interventional technique for recanalization of complex chronic central venous total occlusions is described to overcome difficulties in case of failure of common approaches. Method: We present a patient with a central venous occlusion that caused severe venous congestion of her upper extremity and significant impairment of her forearm hemodialysis shunt. Since the usual transbrachial and transfemoral attempts for recanalization of occluded right subclavian, brachiocephalic, superior vena cava, and proximal internal jugular veins (IJV) failed, the approach was changed to a transjugular access. Only the IJV and subclavian vein occlusions were passed from transjugular. Results: The key procedure was the switch of a jugular-brachial wire to a femoral-brachial setting. The wire transposition was achieved by snaring the looped stiff end of the jugular-brachial wire outside the jugular sheath from the opposite femoral access. Conclusion: Different approaches should be considered for the recanalization of challenging central venous occlusions. After failed attempts via common access sites, a guidewire transposition maneuver using a combined approach may be particularly helpful for safe and effective endovascular treatment of complex situations.